Polygamy Legal Politics in Southeast Asian Muslim Countries: Legal Pluralism and Qur'anic Perspectives - Naqiyah; Triana, Nita; Zakaria, Gamal Abdul Nasir; Liddini, Laily (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
Polygamy regulations are designed to protect the interests of Muslim families; however, ironically, in some Muslim countries, these regulations have been associated with triggering domestic violence. This study aims to examine the legal politics of polygamy in Southeast Asian Muslim countries: Indonesia, Malaysia, and Brunei Darussalam using a legal pluralism approach alongside Qur'anic perspective. The methodology employed is qualitative with a descriptive-interpretative approach. The findings indicate that these three countries regulate polygamy through two reforms: intra-doctrinal reforms that accommodate religious and cultural norms and extra-doctrinal reforms encompassing legal frameworks, judicial systems, and institutional structures. Three main factors influence these legal policies: religious understanding, local traditions, and political and social dynamics. As ūlū al-amri (authoritative leaders), the governments of these countries are committed to regulating polygamy to benefit families and children by integrating Islamic values, local traditions, and colonial legal influences. These regulations align with the Qur'anic message that permits polygamy under certain conditions and strict requirements, aiming to achieve marital goals of tranquility (sakīnah), affection (mawaddah), and compassion (raḥmah). However, stricter supervision and substantive legal reforms are necessary to reinforce these requirements and impose sanctions on violators.